Hedonic Eating Goals and Emotion: When Sadness Decreases the Desire to Indulge - Salerno, Anthony; Laran, Juliano; Janiszewski, Chris (Journal of Consumer Research, 2014)
This article uses the functionalist perspective of emotion to demonstrate that the influence of sadness on indulgent consumption depends on the presence of a hedonic eating goal. Sadness heightens a person's sensitivity to the potentially harmful consequences of indulgent consumption, which decreases indulgence when a hedonic eating goal is salient. As sadness is often associated with a loss, this protective function is geared toward preventing future losses. The execution of this function is mitigated by feelings of safety, a counterforce to concerns about the harmful consequences of goal pursuit. Alternatively, when a hedonic eating goal is not salient, or a salient goal does not have harmful consequences, sadness results in emotion regulation (i.e., indulging as a means of feeling better). This conceptualization and findings show that the effects of emotions on indulgent consumption can be goal-dependent, and that emotions can aid consumers in the balancing of long-term goals and well-being.